Eosinophilic Pneumonia Triggered by Toxocara canis in a Patient with Primary Ciliary Dyskinesia: A Clinical Case Report - Kacper Packi; Wanda Fugiel; Violetta Gołąbek; Alicja Rudek; Agnieszka Śliwińska (Medicina)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder that affects the structure and function of cilia, primarily impacting the respiratory system. Kartagener syndrome, a subset of PCD, is characterized by situs inversus, bronchiectasis, and chronic sinusitis. Patients with PCD are prone to recurrent respiratory infections due to impaired ciliary function, which hinders effective mucus clearance and promotes pathogen colonization. This case report describes a 24-year-old woman with congenital Kartagener syndrome who developed eosinophilic pneumonia caused by Toxocara canis, a rare parasitic infection that less commonly affects the lungs. Despite initial treatment for a presumed bacterial infection, the patient’s symptoms persisted. Further diagnostics revealed elevated eosinophil counts, total IgE, and the presence of Toxocara canis antibodies. The patient was treated with albendazole, resulting in significant symptom improvement and a reduction in inflammatory markers. This case underscores the diagnostic challenges in treating PCD patients, where atypical infections must be considered, particularly when standard treatments prove ineffective. The complexity of the patient’s condition required interdisciplinary management, integrating parasitological, immunological, and respiratory expertise to ensure appropriate treatment. The case highlights the need for further research into the interactions between congenital respiratory disorders such as Kartagener syndrome and parasitic infections. It also emphasizes the importance of a comprehensive diagnostic approach in managing rare genetic diseases complicated by opportunistic infections. Early detection of parasitic infections in PCD patients is crucial to preventing severe complications, and this case reinforces the necessity of considering parasitic causes in atypical pneumonia cases.